Flexing sebagai Simulakra Status Sosial di Era Digital - Nandea Khodijah; Vini Anggun Pratiwi; Maulana, Ridho Adji; Sununianti, Vieronica Varbi; Istiqoma Istiqoma; Kurniawan, Deni Aries (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the phenomenon of flexing on social media as a representation of social status in digital society through the perspectives of Jean Baudrillard’s simulacra theory and Erving Goffman’s self-presentation theory. The research employs a qualitative method using content analysis of social media posts, particularly on Instagram and TikTok, that display flexing practices. The research data consist of photos and videos containing symbols of luxury, such as branded goods, luxury vehicles, exclusive locations, and consumptive lifestyles. The findings reveal that flexing is not merely an act of showing off, but also a conscious self-representation strategy used to construct a particular social image. The luxury symbols displayed often do not fully reflect reality, but rather represent identity constructions that have been selectively curated and manipulated according to the desired image. From the perspective of simulacra, these representations have replaced reality itself, causing the boundary between reality and representation to become increasingly blurred. Furthermore, the phenomenon of flexing is closely related to consumer culture, the need for social recognition, and personal branding strategies in the digital era. Exposure to flexing content also encourages social comparison, which may lead to psychological pressure among audiences. Therefore, flexing can be understood as a multidimensional phenomenon reflecting changes in how individuals construct identity, perceive reality, and gain social legitimacy within digital society.